PERLINDUNGAN HUKUM BAGI KONSUMEN PDAM SURYA SEMBADA KOTA SURABAYA ATAS PENETAPAN TARIF DALAM KONTRAK BAKU - Raden Riyan Budi Setiawan; M.Revendra Diva Firdiansyah; Maulana Syarif Hidayatullah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Development in Indonesia is a complete human development, namely development in all fields, considering that economic development and development in general and especially development in the business sector is increasing, unhealthy business competition will inevitably arise both between one business actor and another business actor and between business actors and consumers. One of the business entities engaged in these services is the Regional Drinking Water Company (PDAM) which is a business entity engaged in clean water supply services. Where related to its grievances as a business entity oriented towards profit-oriented on the one hand, and protection of consumers on the other hand is a juridical issue that needs to be considered. The legal relationship that arises between PDAM business actors and consumers as users of water services is a legal relationship born from contractual, where the type of contractual is a standard contract or standard contract, by looking at the concept of a standard contract, it can be seen that the position of one of the parties, in this case, the consumer is in a very weak position because consumers are only given two choices, namely agreeing or disagreeing with the contract. Some PDAMs issued a unilateral tariff increase policy and imposed new tariffs that experienced a significant increase from the old tariff provisions. This tariff increase is considered a unilateral policy so the position of consumers as users of water services in standard contracts is greatly harmed by the unilateral tariff policy. The formulation of the problem in the paper is How is the legal protection of consumers for unilateral tariff determination by PDAM? Based on the results of the study, consumer legal protection for tariff determination carried out unilaterally in standard contracts by PDAMs is regulated in Law Number 8 of 1999 concerning Consumer Protection and Permendagri Number 23 of 2006 concerning Technical Guidelines and Procedures for Regulating PDAM Drinking Water Tariffs. Based on Law Number 8 of 1999, consumers can file a lawsuit civilly with the District Court (PN) or the Consumer Dispute Resolution Agency (BPSK) based on a legal relationship born of contractual origin. Meanwhile, based on Permendagri Number 23 of 2006, if the decision of the Regent and/or Mayor regarding the tariff increase is contrary to Permendagri Number 23 of 2006, it can be sued for cancellation of the decree in the State Administrative Court (PTUN).